Surface modification of additive manufactured components by ultrasonic cavitation abrasive finishing - Tan, Kai Liang (2017)
Powder Bed Fusion (PBF) is a group of powder-bed based layered Additive Manufacturing (AM) techniques for direct fabrication of metal and metal alloys. Despite its advancements, the surface quality of as-built PBF components remains unsatisfactory. In this paper, a new post-process finishing technique, based on ultrasonic cavitation effects in a solid-liquid mixture, is introduced for PBF-built components. Trials were conducted on side surfaces of Inconel 625 manufactured by Direct Metal Laser Sintering (DMLS). Results have demonstrated that this technique improves Ra values of as-built Inconel 625 side surfaces by up to 45% after 30 min of processing time. Scanning electron microscopic images revealed that most small-sized partially melted powders were removed through heterogeneous cavitation nucleation on the specimens’ rough initial surface. A secondary fine-scale erosion mechanism by micro-abrasives, accelerated by cavitation bubble collapses, further depressed difficult-to-remove irregularities.